The Meaning of Microloans for Families with Economic Limitations: A Qualitative Study of Bank Mekar Customers - Shine Kurdiati Miare; Dewien Agustin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Economic inequality in rural Indonesia remains a significant challenge, especially for low-income families who have limited access to formal financial institutions. Microcredit emerges as an accessible alternative solution, particularly for women who manage household finances. This study was conducted in Simongagrok Village, Dawarblandong District, Mojokerto Regency, aiming to understand the meaning and utilization of microloans among housewives who are clients of Bank Mekar. Using a qualitative approach and Max Weber’s social action theory, the research explores the experiences, motivations, and strategies of women in obtaining and managing microloans. Findings reveal that microloans are predominantly used for daily consumption needs and debt repayment rather than productive business capital. Women play a central role as household managers, combining economic rationality with socio-cultural values. Social solidarity within borrower groups provides support as well as psychological pressure. The cycle of debt and strict repayment obligations create tension between aspirations for economic independence and the reality of financial constraints. This study emphasizes that microcredit is a complex socio-economic phenomenon that must be understood within the cultural and social structures of poor rural communities.